URGENSI NILAI-NILAI RELIGIUS DALAM KEHIDUPAN MASYARAKAT HETEROGEN DI INDONESIA - Umar, Mardan (Universitas Negeri Manado, 2019)
The focus issue in this discussion is how the urgency of fostering religious values in public life heterogeneous in Indonesia and how to provide guidance in religious values in public life heterogeneous in Indonesia ?. The purpose of this study was to describe the urgency of fostering religious values in public life heterogeneous in Indonesia and to provide guidance in religious values in the life of a heterogeneous society in Indonesia. The results of this study indicate that the Indonesian people have an emphasis in terms of harmony in the lives of its people. This can be seen in the first principle of Pancasila that Almighty God. Therefore, development of religious values in public life Indonesia is considered very important. Formation of religious values can be reached through religious education to reinforce faith in the truth of religion and its values. In addition, the formation of religious values do habituation through worship that is manifested in the behavior of everyday life. Fostering religious values also need to be supported by the appreciation of the values of religion since from the family, school and community.Keywords: building, value, religious, heterogeneous.